THE EFFECT OF INVESTMENT DECISIONS ON COMPANY VALUE IN LQ45 INDEX COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2020 PERIOD - ESY MURTIANUR ESY (Indragiri Research Center (ingreat), 2023)
This study aims to examine the effect of investment decisions on firm value in LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period as measured by financial ratios to firm value and to test whether investment decisions are measured by Fixed Assets to Total Assets (FATA) and investment decisions as measured by the Price Earning Ratio (PER) affect the company value of the LQ45 index as measured by Price To Book Value (PBV). This research was conducted on LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period as many as 45 companies and sampling using the purposive sampling, 27 companies that meet the criteria. Data collection methods used are Library Research and Web Searching. The data analysis used was SPSS V23, while the data management was the classical assumption test, multiple linear regression analysis and hypothesis testing. From the results of research using the coefficient of determination test (R2) obtained a yield of 12.5%. FATA and PER affect Firm Value (PBV), while the remaining 87.5% are influenced by other variables not examined in this study. Based on the results of the t (partial) test for variables Price Earning Ratio have tcount<ttable or 2,933 < 1,67022 then H0 rejected and Ha accepted and the sig value of 0.005 is smaller than 0.05 so it can be concluded that Price Earning Ratio significant effect on firm value, and Fixed Asset to Total Asset have tcount>ttableor -1,432 > 1,67022 then H0 accepted and Ha rejected and the sig value of 0.157 is greater than 0.05 so it can be concluded that partially Fixed Asset to Total Asset there is no significant effect on Firm Value. And from the F test (simultaneous) Price Earning Ratio and Fixed Asset to Total Asset Fcount>Ftableor 4.428 > 2.75 with a significant value of 0.016 less than 0.05, it can be concluded that simultaneously there is a significant effect on firm value at LQ45 index companies listed on the Indonesia Stock Exchange for the 2018-2020 period.